GAMBARAN PENGETAHUAN DAN KEJADIAN SEXUAL BULLYING PADA SISWA-SISWI KELAS XI DAN XII DI SMA MUHAMMADIYAH 2 SURABAYA - Yulia Shofiatul Labibah; Aim Matun Nadhiroh; Irma Maya Puspita (Midwifery Care Journal, 2026)
Sexual bullying is one of the phenomena that often occurs today. The sexual bullying is a form of bullying, oppression, harassment of a person's gender and sexuality that the normalization of behaviour makes the number of sexual bullying incidences. Since, there has been no special attention in handling it seriously.  Good understanding can be used as one of the efforts to avoid sexual bullying. The purpose of this research found out the characteristics of students, the level of knowledge of students about sexual bullying and the incidence of sexual bullying in SMA Muhammadiyah 2 Surabaya. The type of research used descriptive quantitative approach. This research was conducted in September 2024 at SMA Muhammadiyah 2 Surabaya. The sampling technique used cluster sampling with a sample of 262 students in grades XI and XII. The results showed that most of the students had a low level of knowledge as many as 140 people (53.4%) and there were 141 (53.8%) incidents of sexual bullying in students in grades XI and XII with the most type being cyber sexual bullying which was 85 (60.3%). Based on the results of the research, it was hoped that students of SMA Muhmmadiyah 2 Surabaya would receive education related to sexual bullying and its impact on adolescent reproductive health as an effort to reduce the incidence of sexual bullying.